In the footsteps of Latin American Sociology in the second half of the 20th century: Notes of two essays by Agustín Cueva Dávila - Quevedo Ramírez, Tomás (Sociología y Política HOY, 2022)
This article analyzes the essays Sobre exilios y reinos I (1984) and II (1988), written by the Ecuadorian sociologist Agustín Cueva Dávila and looks for the traces of Latin American sociology in the 1960s and 1980s. The work of this author allows us to investigate the main theoretical currents and the transformations of sociology as a field of knowledge. Where the conflictive political conjunctures of the period influence the radicalization of those who act in the sociological field, but also in its unexpected turns to the right. In short, from these essays and memoirs by Cueva it is possible to discuss the meaning of "doing sociology" in times of crisis, when conservative thought is gaining ground in public debate. Towards the end of the article, a brief reflection on the future of Ecuadorian sociology, from Cueva's perspective, is added.